2017
DOI: 10.1097/hjh.0000000000001274
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of carotid artery reactivity with cardiovascular risk factors and coronary artery vasodilator responses in asymptomatic, healthy volunteers

Abstract: Objectives. Carotid artery reactivity (CAR%), involving carotid artery diameter responses to a cold pressor test, is a non-invasive measure of conduit artery function in humans. This study examined: 1. the impact of age and cardiovascular risk factors on the CAR% and 2. The relationship between CAR% and coronary artery vasodilator responses to the cold pressor test. Methods. Ultrasound was used to measure resting and peak carotid artery diameters during the cold pressor test, with CAR% being calculated as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 34 publications
8
62
0
Order By: Relevance
“…This finding implies that there might be geographical variation in carotid artery size between patients in northern and southern China. The geographical variation in carotid artery size could be explained by the differences in the genetic diversity or environmental factors (such as temperature) 17 18. In the present study, we also found that after adjusting for height, the differences in absolute vessel dimensions between subjects in northern and southern China decreased, suggesting that this phenomenon might be derived at least in part from the differences in body size rather than atherosclerotic disease in the arterial wall.…”
Section: Discussionsupporting
confidence: 63%
“…This finding implies that there might be geographical variation in carotid artery size between patients in northern and southern China. The geographical variation in carotid artery size could be explained by the differences in the genetic diversity or environmental factors (such as temperature) 17 18. In the present study, we also found that after adjusting for height, the differences in absolute vessel dimensions between subjects in northern and southern China decreased, suggesting that this phenomenon might be derived at least in part from the differences in body size rather than atherosclerotic disease in the arterial wall.…”
Section: Discussionsupporting
confidence: 63%
“…For example, sympathetic stimulation is known to cause dilation in both the coronary and carotid arteries in healthy individuals, whilst this deteriorates to vasoconstriction in those with coronary artery disease [2]. Moreover, the potential link between coronary and carotid artery health was recently reinforced by Van Mil and colleagues [3], who found moderate-to-strong correlation between carotid artery and coronary artery responses to sympathetic stimulation. Finally, one previous study found that 4-weeks of exercise training in patients with coronary atherosclerosis attenuated the coronary vasoconstrictive response to acetylcholine-infusion [8].…”
Section: Discussionmentioning
confidence: 99%
“…The peak diameter and CARAUC refers to a constriction or dilation. Between day coefficient of variation for CAR% has been reported as 2.8% [3].…”
Section: Measurements (Carotid and Brachial Artery Vascular Function)mentioning
confidence: 99%
See 2 more Smart Citations